RARE DISEASES OF THE BLOOD SYSTEM: A CLINICAL CASE OF VIRUS-ASSOCIATED BONE MARROW APLASIA IN A PATIENT WITH A HEREDITARY MEMBRANOPATHY (REVIEW) - A. V. Zabela; V. S. Selivanov; T. N. Babaeva; I. B. Kovynev (Сибирский научный медицинский журнал, 2019)
The aim of study was to research and present literature data regarding the investigations of some combined types of anemia in pregnancy and to describe the clinical case of pregnancy associated with primary parvovirus B19 infection and newly diagnosed hereditary erythrocyte membrane disorder. The contemporary information about the etiology, the prevalence, structure and some features of pathogenesis of parvovirus infection based on literature data was given. The huge prevalence of this infection (according to data of different sources the serum level of parvovirus B19 specific antibodies may be detect in 90 % of population), its threat for fetus and risk of severe complications in patients with immunodeficiency, as well as possibility of development of total depression of hematopoiesis in patients with hereditary erythrocyte membrane disorders, such as Minkowsky-Chauffard disease, determine the relevance and significance of the discussed topic. Furthermore, this clinical case, which illustrates the features of primary parvovirus B19 infection in patient with hereditary hemolytic anemia and the difficulties of differential diagnosis, demonstrates the importance of parvovirus infection markers detection, which is not available in the most TORCH-panel.